Notices (Blackfriars, 1934)
On the Power of God. Quæstiones Disputatæ de Potentia Dei. By St. Thomas Aquinas. Die Geschichte der katholischen Theologie seit dem Ausgans der Vaterzeit von Dr. Martin Grabmann. Studies in the Gospel of St. John. By the Very Rev. H. Erskine Hill, D.D. The Evangelical Approach to Rome. By Stanley B. James. A Second Sheed and Ward Anthology. L'Ave Maria avec Bernadette. By R. P. Piacentini. Antonito: A Spanish Boy of 1'0-DAY. By Fr. Benedict Williamson. Thoughts from St. Benedict. Edited by Maurice Leahy. A Newman Prayer Book. Compiled by Ada F. Clarke. O Perfect Love and other Religious Verses. By Dorothy Gurney. God's Garden and other verses. By Dorothy Gurney. Your Hidden Powers. By Alan Macey. House of Faith. Verses by James O'Hanlon Hughes, F.R.I.B.A.